Ultrasound-Guided Thermal Ablation of Bethesda IV Thyroid Nodules: A Pilot Study - Li, Xinyang; Lan, Yu; Li, Nan; Yan, Lin; Xiao, Jing; Zhang, Mingbo; Luo, Yukun (Frontiers in Endocrinology, 2021)
Objective: The Purpose of our study was to evaluate the effectiveness of thermal ablation (TA) for Bethesda IV thyroid nodules, and to compare TA and surgery in terms of treatment outcomes, complications and costs. Method: This study was approved by the local ethics committee. From January 2017 to December 2019, 30 patients elected TA and 31 patients elected surgery for treatment of Bethesda IV thyroid nodules. Demographics Information and conventional ultrasound before treatment for each patient was obtained. For the TA group, the ablation extent was 3 mm beyond the edge of the tumor to prevent marginal residual and recurrence. And patients were followed up at 1, 3 and 6 months after intervention, and every 6 months thereafter. Postoperative complications, operation time, hospitalization time, the blood loss and incision length were recorded. Results: In the TA group, the volume reduction ratio (VRR) was 94.63±8.99% (range:76%-100%) at the final follow-up. The mean follow-up time was 16.4±5.2months (range:12–24 months). No recurrences, no metastatic lymph node and distant metastases were detected during follow-up. The TA group had fewer complications, shorter operation time, smaller incision length, less blood loss, shorter hospitalization time, and lower treatment costs compared to the surgery group (all P＜0.001). Conclusions: TA is technically feasible for the complete destruction of Bethesda IV thyroid nodules, and also safe and effective during the follow-up period, with high VRR and low complication rates, especially in patients who were ineligible for or refused surgery.